Amphiphilic Graft Copolymers as a Versatile Binder for Various Electrodes of High‐Performance Lithium‐Ion Batteries. Issue 23 (27th April 2016) - Lee, Jung‐In; Kang, Hyojin; Park, Kwang Hyun; Shin, Myoungsoo; Hong, Dongki; Cho, Hye Jin; Kang, Na‐Ri; Lee, Jungho; Lee, Sang Myeon; Kim, Ju‐Young; Kim, Choon Ki; Park, Hyesung; et al.
Abstract : It is known that grafting one polymer onto another polymer backbone is a powerful strategy capable of combining dual benefits from each parent polymer. Thus amphiphilic graft copolymer precursors (poly(vinylidene difluoride)‐ graft ‐poly( tert ‐butylacrylate) (PVDF‐ g ‐PtBA)) have been developed via atom transfer radical polymerization, and demonstrated its outstanding properties as a promising binder for high‐performance lithium‐ion battery (LIB) by using in situ pyrolytic transformation of PtBA to poly(acrylic acid) segments. In addition to its superior mechanical properties and accommodation capability of volume expansion, the Si anode with PVDF‐ g ‐PtBA exhibits the excellent charge and discharge capacities of 2672 and 2958 mAh g −1 with the capacity retention of 84% after 50 cycles. More meaningfully, the graft copolymer binder shows good operating characteristics in both LiN0.5 M1.5 O4 cathode and neural graphite anode, respectively. By containing such diverse features, a graft copolymer‐loaded LiN0.5 M1.5 O4 /Si‐NG full cell has been successfully achieved, which delivers energy density as high as 546 Wh kg −1 with cycle retention of ≈70% after 50 cycles (1 C). For the first time, this work sheds new light on the unique nature of the graft copolymer binders in LIB application, which will provide a practical solution for volume expansion and low efficiency problems, leading to a high‐energy‐density lithium‐ion chemistry. Abstract : High energy density lithium ion batteries including a high voltage cathode (LiNi0.5 Mn1.5 O4 ) and high capacity anode (3D‐porous Si) are fabricated with amphiphilic graft copolymer via atom transfer radical polymerization transfer. The battery delivers a high energy density of about 546 Wh kg −1 with good cycling stability at a rate of 1 C.